The post-modern Japanese identity of Haruki Murakami's literature. - Ling, Shannon. (2013)
The year was 1889 when William Butler Yeats, arguably one of the foremost important figures in 20th century literature, declared that “there is no fine nationality without literature, and… no fine literature without nationality” (Allison 238). Regarded as the literati ahead of his contemporaries, his words would come to ring true in the following century, as the concept of identity (and national identity) would rise to the forefront of most literature coming out of East Asia, with the traditions and cultures of these nations challenged by the onset of modernization (or Westernization) into the region. Japan, in particular, had undergone massive changes since the end of the Meiji era and the Second World War, giving birth to a new generation of Japanese torn between respecting the traditional and embracing the modern. And for the modern Japanese writers like Haruki Murakami, this conflict presents a pertinent issue with his literature often derided by Japanese scholars and writers alike for the failure to represent the real Japan in his novels.In the first part of my thesis, I would seek to explore the influence that the writer himself has on his writing, discussing a little about his history such as the generation of Japanese that he was borne into. At the same time, I would also look at the particular genre of detective fiction in a critical component in understanding Murakami’s writings, as well as his fondness of music and how shapes his style of writing and in symbolizing the search for the identity. The second part would deal primarily with the theory of dualism and how it is related to the concept of identity in Murakami’s literature, primarily through a series of examples of the theory used by the writer in illustrating his point. The third and final part would then focus on the reconciliation of the identity, and what should be made of this new identity that Murakami has recreated through his novels, and its standing as the embodiment of contemporary Japan in context with its globally-connected society that exists today